On the nonabelian tensor square and capability of groups of order p2q - Rashid, S. (SP Birkhäuser Verlag Basel, 2011)
A group G is said to be capable if it is isomorphic to the central factor group H/Z(H) for some group H. Let G be a nonabelian group of order p 2 q for distinct primes p and q. In this paper, we compute the nonabelian tensor square of the group G. It is also shown that G is capable if and only if either Z(G) = 1 or p < q and Gab=Zp×Zp .